Crystal structure of signal regulatory protein gamma (SIRPγ) in complex with an antibody Fab fragment - Nettleship, Joanne E.; Ren, Jingshan; Scott, David J.; Rahman, Nahid; Hatherley, Deborah; Zhao, Yuguang; Stuart, David I.; Barclay, A. Neil; Owens, Raymond J. (BioMed Central, 2013)
BACKGROUND